2018
DOI: 10.1016/j.bcp.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitor suppresses proliferation and invasion of breast cancer cells through regulation of miR-200c targeting CRKL

Abstract: Although histone deacetylase (HDAC) inhibitors have been shown to effectively induce the inhibition of proliferation and migration in breast cancer, the anticancer mechanism remains poorly understood. Our studies show that miR-200c was significantly downregulated in breast cancer cell lines compared to normal cell lines and inversely correlated with the levels of class IIa HDACs and CRKL. HDAC inhibitors and the ectopic expression of miR-200c as tumor suppressors inhibited the proliferation, invasion, and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 51 publications
(50 reference statements)
0
40
0
Order By: Relevance
“…miRNAs are a class of small noncoding RNAs with 18-25 nucleotides, which play as promising targets for diagnosis, prognosis and therapeutics of breast cancer [12]. Previous works have demonstrated that miR-200b and miR-200c could serve as important tumor suppressor by inhibiting cell proliferation, migration and invasion in breast cancer [13][14][15][16][17]. More importantly, the complementary sites between cir-cDENND4C and miR-200b or miR-200c predicted by bioinformatics analysis using starBase stimulated us to hypothesize that miR-200b and miR-200c might be required for circDENND4C-mediated progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are a class of small noncoding RNAs with 18-25 nucleotides, which play as promising targets for diagnosis, prognosis and therapeutics of breast cancer [12]. Previous works have demonstrated that miR-200b and miR-200c could serve as important tumor suppressor by inhibiting cell proliferation, migration and invasion in breast cancer [13][14][15][16][17]. More importantly, the complementary sites between cir-cDENND4C and miR-200b or miR-200c predicted by bioinformatics analysis using starBase stimulated us to hypothesize that miR-200b and miR-200c might be required for circDENND4C-mediated progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 MiRNAs can repress the protein expression via mRNA degradation or translational inhibition through binding to the 3′-untranslated regions (3′-UTRs) of mRNAs. [6][7][8][9][10][11] BMI1 is a member of polycomb repressive complex 1 that has multiple roles in chromatin modification, DNA damage repair, cell cycle regulation, and senescence. Upregulated miRNAs are considered as an oncogene and downregulated miRNAs as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-200c is a tumor suppressor which inhibits the proliferation, EMT, migration, and invasion and induces the apoptosis and chemosensitivity in various cancers, such as renal cell cancer, ovarian cancer, bladder cancer, ovarian cancer, and CRC. [6][7][8][9][10][11] BMI1 is a member of polycomb repressive complex 1 that has multiple roles in chromatin modification, DNA damage repair, cell cycle regulation, and senescence. Furthermore, BMI1 is involved in cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ZEA, OTA, and AFB1 may increase the incidence of human breast cancer (Yip, Wan, Wong, Korach, & El‐Nezami, ; Yu, Zhang, Wu, & Liu, ), and a metabolite of ZEA, α‐ZAL, may play a key role in the development of breast cancer (Belhassen et al., ). Further, miR‐21, let‐7, miR‐200c, and miR‐199a can regulate the development of breast cancer, thus, they may function as feasible diagnostic biomarkers and therapeutic targets for mycotoxin‐induced breast cancer (Bian, Liang, Feng, Salgado, & Shim, ; Elghoroury et al., ; Xu et al., ).…”
Section: Mirna and Diseases: Are They Related To Mycotoxins?mentioning
confidence: 99%
“…Since the known molecular mechanisms underlying the pathogenicity and carcinogenicity of mycotoxin are mostly at the protein level, very few examinations on miRNAs (likely the aberrant expressed miRNAs) can be found for early diagnosis of acute toxicity induced by mycotoxin. -122, miR-34a, miR-192, miR-26b, miR-761, miR-21, miR-199a ZEA, AOH, 3-ADON, 15-ADON, AFB1, FB1 (Gazzah et al, 2013;Juan-García et al, 2015;Qian et al, 2016;Girard et al, 2008;Brzuzan et al, 2015;Zhao et al, 2014;Zhou et al, 2016;Amr et al, 2016) Breast cancer miR-21, let-7, miR-200c, miR-199a ZEA, OTA, AFB1, α-ZAL (Yip et al, 2017;Yu et al, 2005;Belhassen et al, 2015;Bian et al, 2017;Elghoroury et al, 2017;Xu et al, 2017) Colon carcinoma miR-378-3a, miR-21, miR-34a, miR-299-3p, miR-495, miR-199a-5p, miR-375, miR-136, miR-15a, miR-192 DON, ZEA (Bensassi et al, 2009;Abassi et al, 2016;Fang et al, 2017;Kara et al, 2015;Wang et al, 2017;Yan et al, 2017;Yuan et al, 2017;Brzuzan et al, 2015) Inflammation-related diseases miR-21, miR-130a, miR-132, miR-155, miR-221 ZEA, DON, OTA, Patulin (Fan et al, 2018;Tardivel et al, 2015;Marin et al, 2017;Kim et al, 2015;McDonald et al, 2015;Croston et al, 2018;Qi et al, 2014;Valencia-Quintana et al, 2014) Apoptosis-induced diseases…”
Section: Mycotoxins and Mirnasmentioning
confidence: 99%